Research Innovation Model at the Office of Religious Research and Development Semarang - Sofanudin, Aji; Wahyudi, Andi (Jurnal Bina Praja, 2018)
This research aimed to explore research innovation model in the Office of Religious Research and Development (RRD), Ministry of Religious Affairs (MORA) in Semarang. Research innovation model includes new ideas, practices, and methods in research field to further enhance the quality of research. The new ideas, practices, and methods consist of things that have been implemented, existed and practiced by the research institutions. This research used the qualitative approach and fact-finding method. The data were collected in several ways, such as experience and observation, interview, and secondary data. The result revealed the leader of the Office of RRD Semarang ideas concerning the importance of establishing quality-based policy research. In practice, those ideas were implemented in at least four forms of innovation which are the existences of (1) The Research’s Internal Quality Guarantor Team, (2) Electronic Journals, (3) Collaborative Research and Development, (4) Policy Brief, and (5) MPEP Team. Those innovations were considered as a process and product innovation. Finally, it concluded that the leadership factor had a significant role in this organization to create such innovations.